Eficiência da luz solar refletida e desempenho de dispositivos de sombreamento: estudo para salas de aula na cidade de Maceió - Carvalho, Marlise Lila Silva (2018)
A humid subtropical climate is characterized by a predominant partly cloudy sky, which increases the intensity of solar radiation, and makes shade an essential requeriment. Thus, the indoor daylighting environment may depend more on reflected light than on direct light. Planning the shape of the surfaces is an important means of making full use of the reflected sunlight. In this regard, shading devices can be designed that just obstruct the view of the sky enough to provide shade, by reflecting the sunlight for the environment, and reducing this loss. The aim of this doctoral research is to study the performance of shading devices in classrooms with regard to their luminous power when capturing reflected sunlight in Maceió, so as to determine the potential use of sunlight in these elements. Three variables of these devices were defined for this: the number of pieces, specularity and reflectance of the surfaces devices. The resulting models from the combination of these variables were analyzed to calculate the reflected sunlight efficiency, rate employed in this research. The software used for the computational simulations of these models was TropLux. Statistical analyses were conducted to determine which variables had the greatest impact on the reflected sunlight efficiency and to relate the rate to the daylighting performance through indicators of availability, distribution and the maintenance of illuminance inside the environment: these included the annual average illuminance and uniformity rate, and spatial daylight autonomy. The results showed that the reflectance of the devices is the variable that has the most positive influence on the reflected sunlight efficiency, and is able to increase the rate by up to 142%. The annual average illuminance and the spatial daylight autonomy were positively related to the efficiency and the defined parameterization also led to an increase of their values. With regard to the distribution of illuminances, the variations of the analyzed parameters resulted in a reduction of the uniformity rate in most of the cases studied. The increase in specularity and specular reflectance in the models facing east reduced the rate by up to 34% and 41%, respectively. Increasing the number of components in the system devices installed in lateral openings, only provides a valid solution for the increase of the illumination when these elements have a high reflectance, especially specular. This represents a more efficient strategy in the case of the north facade. Among the analyzed models, in the systems with the largest number of components, and where the surface finishing process provides specular reflection, there is a greater use of sunlight in the reflected form. The use of light colors, such as white, beige and yellow, also benefit the use of sunlight, especially if they are used in materials with specular reflection. In contrast, the high reflectances resulted in a reduction of the uniformity of illumination in the environment. From the results of the studies carried out into reflected sunlight efficiency, it can be stated that it is possible to increase the use of sunlight through the variation of certain shading devices and, hence, to bring benefits by making daylighting available in the environment.